EVALUATION OF E-KTP RECORDING SERVICES FOR NOVICE VOTERS AHEAD OF GENERAL ELECTIONS IN PEKANBARU CITY - Hayati, Rahmadini Sri; Sujianto, Sujianto (PT. Altin Riset Publishing, 2025)
This study aims to analyze and describe the e-KTP recording service for new voters ahead of the general election in Pekanbaru City. This study uses the service theory by Zeithaml, Berry, and Parasuraman which uses 5 indicators, namely tangible, reliability, responsiveness, assurance, and empathy. The application of the method used in this study is a descriptive qualitative research method. With data collection techniques, namely interviews, observation, and documentation. The results of this study are that the e-KTP recording service for new voters ahead of the general election by the Pekanbaru City Popilation and Civil Registry Office is good with the implementation of innovayions that can increase the number of e-KTP recordings, namely outreach efforts. However, there are still several factors that need to be fixed or improved, namely the public awareness, employee accuracy, and technical and operational constraints in outreach efforts.